DEVELOPMENT OF PROFESSIONALISM OF TEACHERS MEANS OF METHODICAL WORK - Sadova, V.V. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of analisis of some potentialities latent in school methodology servise and its possibility to increase tcachers’ professional skills. The expediency in use of block-and-module approach, while choosing (selecting) contents and forms of methodological work organization, is proved.